Clinical Characteristics of Basilar-Type Migraine in the Neurological Clinic of a University Hospital. Issue 7 (24th July 2014) - Ying, Guomin; Fan, Wen; Li, Nan; Wang, Jing; Li, Wangwen; Tan, Ge; Zhou, Jiying
Abstract: Objectives: The aim of this study was to investigate the prevalence and clinical characteristics of basilar-type migraine in the neurology outpatient clinic of a university hospital in China. Methods: This cross-sectional study was conducted in the neurology outpatient of a tertiary care hospital in Chongqing between January 2010 and December 2011. All consecutive patients citing headache as their chief complaint were asked to complete a face-to-face interview by a qualified headache specialist using a detailed questionnaire for headache. The diagnosis of basilar-type migraine was made according to International Classification of Headache Disorders Second Edition. Results: Of the 1, 526 headache patients, 23 (1.5%) were diagnosed with basilar-type migraine (19 women, four men). Basilar-type migraine occurred in 6.6% (23/348) of patients with migraine with nonhemiplegic aura. Mean age at onset was 20.3 ± 11.7 years (range 6–49 years). Among these patients, 65% (15/23) reported bilateral pain, 35% (8/23) unilateral pain. The basilar-type aura comprised diplopia 52%, vertigo 43%, tinnitus 43%, bilateral visual symptoms 39%, hypacusia 26%, ataxia 26%, dysarthria 22%, bilateral paresthesias 13%, and decreased level of consciousness 13%. Intense emotional stimuli (74%) and sleep disorders (65%) were the most common trigger factors, followed by change in weather, sunshine, cold wind, acute stress, alcohol, and fatigue. Conclusion: Basilar-type migraine is an episodic disorder and occurred in 1.5% of patients with headache. More than one-half of patients have their first attack in the second and third decade of life. Trigger factors were common, and patients should be educated to avoid trigger factors.